PENGARUH PENERAPAN E-FILLING, TINGKAT PEMAHAMAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DALAM MELAPORKAN SPT (STUDI KASUS PADA KPP PRATAMA BANDA ACEH) - Cici Vidya Saila; Adnan Adnan (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
This study aims to examine the effect of e-filling implementation, the level of tax understanding on individual taxpayer compliance in reporting SPT (case study on KPP Pratama Banda Aceh). The population in this study are registered taxpayers in the Tax Office Banda Aceh.The population in this study is taxpayers registered as user e-filing taxpayers in KPP Pratama Banda Aceh the number of samples in this study is 85 respondent. Data and information gathered in this study was done by doing field research. The sampling technique used incidental sampling method. Questionnaires were tested by validity test and reliability test before this study. Classic assumption test were used is normality test, linearity test, multicolinearity test, and heteroscedasticity test. The data used in this study are the data which was obtained directly from respondents by distributing questionnaires. The influence test of independent variables to dependent variable was done by using multiple linear regression model. The results showed that the implementation of e-filling, the level of tax understanding are simultaneously affected the compliance of individual taxpayers in reporting SPT in KPP Pratama Banda Aceh.